Skin lesions in acute myeloid leukaemia – case report - Badzian, Aleksandra; Ciuruś, Magdalena; Malinowska, Alicja; Znajewska, Aleksandra; Brycka, Natalia; Grzanka, Aleksandra A.; Placek, Waldemar (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Acute myeloid leukaemia is a malignant neoplastic disease of white blood cells. About 80% of acute leukaemias in adult are diagnosed as myeloid leukaemias. The presence of transformed cell clones in bone marrow and blood, which originate from very early stages of myelopoiesis, is characteristic. Beside systemic symptoms (anaemia, thrombocytopenia) there are infiltrations in other organs, including skin. Skin lesions are most frequently non-specific (pruritus, skin spots, erythema multiforme, bullous pemphigoid) but can be also specific (skin tumours). Cases of diffuse xanthomatoses and myeloid sarcoma have also been found in patients with acute myeloid leukaemia. Skin lesions are present more often in lymphocytic than myeloid leukaemias. They may precede the disease or its relapse, occur concomitantly or after systemic symptoms, and sometimes may be of prognostic value. Objective . To present the case of a patient in whom skin lesions were the cause of detailed examinations, which revealed acute myeloid leukaemia. Case report . We present a case of a 61-year old patient with purple-brown nodular lesions 1-3 cm in diameter on the face, scalp skin, trunk, limbs and the oral cavity’s mucous membranes with coexistent intense pruritus and generalized lymphadenopathy. The first skin lesions occurred three months earlier. During hospitalization in the Department of Dermatology the renewal of blasts in the circulatory blood was observed and skin biopsy revealed a large amount of mononuclear cells. The patient was directed to the haematological ward, where the diagnosis of acute myeloid leukaemia was established. Conclusions . Our case indicates that the presence of skin lesions and thorough diagnostic procedures may contribute to the diagnosis of malignant neoplastic diseases of white blood cells.